(untitled) - Hawley, Louise; Louise Hawley; Richard J. Ziegler; Benjamin L. Clarke (Philadelphia)
BRS Microbiology and Immunology is a popular volume in the Board Review Series for medical students. Written in a concise, readable outline format, this book is intended to cover topics most commonly tested on USMLE. Included are 300 to 500 review questions in the USMLE-style format, and a comprehensive examination
Includes bibliographical references and index
Keywords: Microbiological Phenomena; Immune System Phenomena